Voices : European caravan network manual - Jovcevska, Simona, ....- (The European Caravan, 2025)
The Voices project was a two-year journey in the field of community art. Over 100 young people from five different countries came together, using music and theater as powerful tools to create and foster social change. This manual aims to inspire organizations working in the field, offering practical guidance on how to bring such initiatives to life. It highlights detailed working methods, with a strong emphasis on the integration of music and theater in community work.
Keywords: Buurtwerk